Properties of Lightweight Fiber-Reinforced Alkali-Activated Concrete - Tashima, M. M. [UNESP]; Payá, J.; Borrachero, M. V.; Monzó, J.; Soriano, L. (Elsevier, 2021)
This chapter presents the experimental results regarding the efficiency of using acoustic panels made with fiber reinforced alkali-activated slag foam concrete containing lightweight recycled aggregates produced using an industrial side stream, Petrit-T. The process was developed in a laboratory setting, and its scalability was assessed by an industrial pilot. Hardened state properties were investigated in terms of the mechanical strength (compressive and flexural), drying shrinkage, and sound absorption coefficient. Life cycle assessment (LCA) was also conducted on the produced acoustic panels and the environmental properties of the acoustic panels were compared with the commercial acoustic panels.The experimental results showed that the panels exhibited good acoustic properties to absorb the sound so that the maximum acoustic absorption coefficients for the panels could be varied in the range of 0.5-0.6 in the high frequency regions (4000-5000. Hz). The rate of the drying shrinkage was limited to 25%. μ? after 1100. h and no localized crack was detected on the surface panels. Moreover, LCA revealed that substitution of sodium silicate with other materials considering similar physical and chemical mechanisms and lower negative environmental impacts significantly enhances the sustainability of the acoustic panels.
Keywords: Acoustic panels; Alkali-activated foam concretes; Drying shrinkage; Life cycle assessment; The sound absorption